What temperature is best for the offshore farming of the Australasian snapper, Chrysophrys auratus ? A collective examination of growth, FCR, O 2 consumption and welfare - Selwyn P. Collins; Leonardo J. Magnoni; Denham G. Cook; Suzanne E. Black; Neill A. Herbert (New Zealand Journal of Marine and Freshwater Research, 2025)
The Australasian snapper ( Chrysophrys auratus ) is a candidate for offshore aquaculture in New Zealand. The culture of snapper requires knowledge of the best locations for farms and a key variable is water temperature. The oxygen‐ and capacity‐limited thermal tolerance (OCLTT) hypothesis suggests fish performance is optimised at the temperature that maximises absolute aerobic scope (AAS), whereas the ‘multiple performances–multiple optima’ (MPMO) idea, suggests AAS and other performance measures can have different optimal temperatures. Therefore, the applicability of the OCLTT for snapper was tested by holding juveniles at 15, 18, 21, or 24°C for two months and constructing thermal performance curves (TPCs) for specific growth rate (SGR), feed conversion ratio (FCR) and AAS, and an assessment of welfare indicators. We hypothesised that the OCLTT would apply with all TPCs optimised at 21°C. However, AAS showed no discernible peak with temperature (although lower at 15 than 18°C); SGR and FCR improved non‐linearly with temperature; and welfare indicators varied little with temperature. This lack of aerobic limitation and evidence of MPMO suggests snapper are amenable to culture across a significant temperature range with warmer water likely providing the highest levels of productivity with maintained welfare.

Highly mobile pelagic species co‐occur with fine‐scale ocean fronts - Alexandre Lhériau‐Nice; Denham G. Cook; Alice Della Penna (Limnology and Oceanography, 2025)
Coastal areas are an important source of food and a valuable tourism asset for communities, but also highly dynamic and heterogeneous environments. Understanding how marine species respond to the variability of their habitat is essential to sustainably manage coastal resources. Here we investigate the distribution of highly mobile marine species in relation to fine‐scale fronts ( a fronts for most species considered. Specifically blue mackerel, kahawai, and jack mackerel are most often found in regions of moderate to high chlorophyll a and characterized by strong spatial gradients in ocean color. On the other hand, seabirds and mammals collocated most often with higher chlorophyll a concentrations and lower gradients compared to the other species examined. These findings advance our understanding of how mobile marine species interact with fine‐scale coastal fronts, suggesting that these features and their variability need to be accounted explicitly for habitat modeling and effective management.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Investigating food limitations in wild fisheries: the attendance and growth responses of fish at an anthropogenic feeding station within a temperate estuary - Denham G. Cook; Peter Jaksons; Alistair Jerrett (Journal of Fish Biology, 2020)
To investigate whether wild fish populations are food limited, this study explored whether the provision of supplementary food had a positive effect on the abundance, condition and growth characteristics of estuarine fish assemblages in New Zealand. Feed (7690 kg) was delivered from an anthropogenic feeding station over a 60‐week period to a naturally occurring assemblage of wild fish. Yellow‐eyed mullet ( Aldrichetta forsteri ) of juvenile, sub‐adult and newly matured size classes were the dominant species actively foraging at the feeding station throughout its operation, whereas larger piscivorous species visited and foraged from the feed station over the summer period only. Other species were present in the wider area of Nelson Haven, but not at the feed station. No obvious changes in the condition factor of yellow‐eyed mullet were observed across the period of monitoring, and no changes in their catchability were detected – although marked seasonal variation in catch rates was observed. Results from tag‐recapture data identify that the length‐based growth rates of yellow‐eyed mullet recaptured near the feed station were higher than those of tagged individuals recaptured at a nearby comparison site, and were higher than the growth rates observed in natural populations of yellow‐eyed mullet in the wider region. Shifts in the median size of fish, as observed by acoustic observations, agreed with the tag‐recapture data. Although some of the results identified were not amenable to statistical analyses, the attendance of yellow‐eyed mullet at the feeding station, in combination with the improved estimates of growth by most of the techniques employed, indicates that yellow‐eyed mullet are food limited in their natural environment and that the growth performance of these fish can be positively affected by the increased availability of food.

The effect of temperature and meal size on the aerobic scope and specific dynamic action of two temperate New Zealand finfish Chrysophrys auratus and Aldrichetta forsteri - Tomislav Flikac; Denham G. Cook; William Davison (Journal of Comparative Physiology B, 2020)

Morphology and hydro-sensory role of superficial neuromasts in schooling behaviour of yellow-eyed mullet (Aldrichetta forsteri) - Karen L. Middlemiss; Denham G. Cook; Alistair R. Jerrett; William Davison (Journal of Comparative Physiology A, 2017)

Temperature effects on metabolic rate and cardiorespiratory physiology of the spiny rock lobster (Jasus edwardsii) during rest, emersion and recovery - Leonard G. Forgan; Nicholas P. L. Tuckey; Denham G. Cook; Alistair R. Jerrett (Journal of Comparative Physiology B, 2014)